Comparing television ratings conventions: Australian and American approaches to broadcast ratings - Balnaves, Mark; O'Regan, T. (Australia and New Zealand Communication Association, 2009)
While the broadcast ratings have provided a stable language and technology for talking about and analysing audiences globally there has been surprisingly little attention paid to the sometimes substantial, sometimes minor variations between ratings instruments internationally. In this paper we begin the consideration of differences and similarities between American and Australian approaches to broadcast ratings anchoring these to the nature of the ratings convention developed in each jurisdiction. The parties to the respective conventions in both countries bear a significant family resemblance to each other, but the relative distribution of power among the parties to the convention - ratings companies, broadcasters, advertisers and agencies- gives rise to identifiably different settlements. There arises distinct politics and practices of audience ratings that can tell us much about respective broadcasting systems.